Győző Határ and politics - Mohácsi, János (Acta Carolus Robertus, 2022)
Határ Győző is an outstanding figure in the emigrant literature of the last century. the national disasters that lived through: wars and prisons left their mark on their fate and thinking. The graduate architect, writer, poet, philosopher, music connoisseur, innovator of the language of writing examined with sharp eyes not only the areas he loved, but also the social context around him. The prison of the Rákosi era enriched its knowledge with special experiences. The physical torture suffered in the Marianostra prison and the ensuing social exclusion prompted him to balance the ideologies and principles of the era. After he had no place in Hungary, he was forced to emigrate and published his smuggled manuscripts from Hungary. He never complained about the ordeals he had suffered, but he judged every phenomenon with the eyes of an agnostic razor. Be it the man of the era, the relationship between generations, communism, religion, or just his favorite subject, philosophy. In his works he expressed all his thoughts in an esoteric form and in an esoteric language. Because of the form and language, many quote, but few read his works.